(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article analyzes new approaches to accounting in the context of the digital economy. The study examines the impact of digital technologies on accounting systems, the effectiveness of automation processes, and their role in improving the quality of financial reporting. It is substantiated that the implementation of digital systems reduces human-related errors and expands opportunities for managerial decision-making. The research findings contribute to the further development and practical implementation of digital accounting systems.